The influence of the menstrual cycle, normal pregnancy and pre-eclampsia on platelet activation - Robb, Amy O.; Din, Jehangir N.; Mills, Nicholas N.; Smith, Imogen B. J.; Blomberg, Anders; Zikry, Mariam N. L.; Raftis, Jennifer B.; Newby, David E.; Denison, Fiona C. (Thrombosis and Haemostasis, 2010)
Platelet activation has a key role in mediating thrombotic and inflammatory events. This study aimed to determine the influence of the menstrual cycle, pregnancy and preeclampsia on in vivo platelet activation. Twelve healthy nulliparous, non-smoking women with regular menses were studied over a single menstrual cycle. Twenty-one healthy primigravida pregnant women were studied longitudinally at 16, 24, 32 and 37 weeks gestation and seven weeks post-partum. Sixteen primigravida women with preeclampsia were studied at time of diagnosis and at seven weeks post-partum. Platelet-monocyte aggregates and platelet-surface P-selectin expression were assessed by flow-cytometry. Soluble P-selectin and CD40 ligand (CD40L) were measured by ELISA. Markers of platelet activation did not vary over the menstrual cycle. Platelet-monocyte aggregates were greater in the third trimester of pregnancy compared to non-pregnant women (p=0.003). Platelet surface and plasma soluble P-selectin concentrations increased with gestation (p<0.0001) and were raised by 24 weeks of pregnancy compared to non-pregnant women (p≤0.02 for both) and together with platelet monocyte aggregates, decreased post-partum (p≤0.02). Soluble CD40L concentrations fell in pregnancy, reaching a nadir at mid-gestation (p=0.002). There were no differences in markers of platelet activation between normal and pre-eclamptic pregnancies. In conclusion, platelet activation is increased in pregnancy and increases with gestation but is unaffected by preeclampsia. This suggests that systemic platelet activation is a feature of pregnancy but this is not affected by established preeclampsia.
Keywords: Platelet activation; platelet-monocyte aggregates; pregnancy; preeclampsia